2016
DOI: 10.1007/s00737-016-0691-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in perinatal depression: how far have we come? A systematic review

Abstract: Despite perinatal depression (PND) being a common mental disorder affecting pregnant women and new mothers, limited attention has been paid to the heterogeneous nature of this disorder. We examined heterogeneity in PND symptom profiles and symptom trajectories. Literature searches revealed 247 relevant studies, 23 of which were included in the final review. The most common statistical approaches used to explore symptom and trajectory heterogeneity were latent class model and growth mixture model. All but one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
92
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 51 publications
16
92
1
1
Order By: Relevance
“…One important limitation in the current literature is the lack of analytical attention to specific PND symptoms. Most research on PND has been conducted at the disease level, focusing on the binary classification of PND (i.e., present or absent) or continuous summary scores (Santos, Tan, & Salomon, ). However, patients diagnosed with depressive disorders can differ dramatically in their symptoms (Fried & Nesse, ; Olbert, Gala, & Tupler, ; Santos et al, ).…”
Section: Mental Disorders As Network Of Interacting Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…One important limitation in the current literature is the lack of analytical attention to specific PND symptoms. Most research on PND has been conducted at the disease level, focusing on the binary classification of PND (i.e., present or absent) or continuous summary scores (Santos, Tan, & Salomon, ). However, patients diagnosed with depressive disorders can differ dramatically in their symptoms (Fried & Nesse, ; Olbert, Gala, & Tupler, ; Santos et al, ).…”
Section: Mental Disorders As Network Of Interacting Symptomsmentioning
confidence: 99%
“…Most research on PND has been conducted at the disease level, focusing on the binary classification of PND (i.e., present or absent) or continuous summary scores (Santos, Tan, & Salomon, ). However, patients diagnosed with depressive disorders can differ dramatically in their symptoms (Fried & Nesse, ; Olbert, Gala, & Tupler, ; Santos et al, ). Moreover, risk factors, the underlying biology, impairment of psychosocial function, and life events are differentially related to specific symptom profiles (for a review, see Fried & Nesse, ).…”
Section: Mental Disorders As Network Of Interacting Symptomsmentioning
confidence: 99%
“…Different trajectories, e.g., depression exclusively during pregnancy, exclusively in the postpartum period, or throughout the pregnancy and postpartum, may have different pathogenesis and consequences for the mother as well as for her family. A recent systematic review of 22 longitudinal studies including more than 38,000 women found between two and six different symptom trajectories (Santos, Tan, & Salomon, ). In studies adopting elaborate statistical modeling when determining PND trajectories, a three‐trajectory classes solution is most commonly reported, though many studies also support a five‐trajectory classes solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, the heterogeneity of levels of depressive symptoms in perinatal mothers and those with young children (under 5 years) has been mentioned in several studies and various social and psychological risk factors have been identified in the trajectory of depressive symptoms (Baron, Bass, Murray, Schneider, & Lund, ; Santos, Tan, & Salomon, ; van der Waerden et al., ). Although the effect of intervention was different for each group, the depressive symptoms of perinatal mothers and those with young children could be explained by complex factors, besides the type and effect of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Young children also affect the mothers if they adapt well to the effect of intervention. In addition, mother-child interaction facilitates interventions (Baron, Bass, Murray, Schneider, & Lund, 2017;Santos, Tan, & Salomon, 2017;van der Waerden et al, 2015). Although the effect of intervention was different for each group, the depressive symptoms of perinatal mothers and those with young children could be explained by complex factors, besides the type and effect of intervention.…”
Section: Discussionmentioning
confidence: 99%